Benzo[a]pyrene/aryl hydrocarbon receptor signaling inhibits osteoblastic differentiation and collagen synthesis of human periodontal ligament cells. (6th January 2016) - Monnouchi, S.; Maeda, H.; Yuda, A.; Serita, S.; Wada, N.; Tomokiyo, A.; Akamine, A.
Abstract : Background and Objective: Cigarette smoking has detrimental effects on periodontal tissue, and is known to be a risk factor for periodontal disease, including the loss of alveolar bone and ligament tissue. However, the direct effects of cigarette smoking on periodontal tissue remain unclear. Recently, we demonstrated that benzo[ a ]pyrene (BaP), which is a prototypic member of polycyclic aryl hydrocarbons and forms part of the content of cigarettes, attenuated the expression of extracellular matrix remodeling‐related genes in human periodontal ligament (PDL) cells (HPDLCs). Thus, we aimed to examine the effects of BaP on the osteoblastic differentiation and collagen synthesis of HPDLCs. Material and Methods: HPDLCs were obtained from healthy molars of three patients, and quantitative reverse transcription–polymerase chain reaction were performed for gene expression analyses of cytochrome P450 1A1 and 1B1, alkaline phosphatase, bone sialoprotein and aryl hydrocarbon receptor ( AhR ), a receptor for polycyclic aryl hydrocarbons. We have also analyzed the role of the AhR, using 2‐methyl‐2H‐pyrazole‐3‐carboxylic acid (2‐methyl‐4‐ o ‐tolylazo‐phenyl)‐amide (CH‐223191), which is an AhR antagonist. Results: The treatment of HPDLCs with BaP reduced mRNA expression of osteogenic genes, alkaline phosphatase activity, mineralization and collagen synthesis. The treatment with CH‐223191 subsequently restored the observed suppressive effects of BaP on HPDLCs. Conclusions: The present results suggest that BaP exerts inhibitory effects on the maintenance of homeostasis in HPDL tissue, such as osteoblastic differentiation and collagen synthesis of HPDLCs, and that this signaling pathway could be suppressed by preventing the transactivity of AhR. Future studies may unveil a role for the inhibition of AhR as a promising therapeutic agent for periodontal disease caused by cigarette smoking.